Hippocampal Volume and Plasma Brain-Derived Neurotrophic Factor Levels in Patients With Depression and Healthy Controls - Fujii, Rintaro; Watanabe, Keita; Okamoto, Naomichi; Natsuyama, Tomoya; Tesen, Hirofumi; Igata, Ryohei; Konishi, Yuki; Ikenouchi, Atsuko; Kakeda, Shingo; Yoshimura, Reiji (Frontiers in Molecular Neuroscience, 2022)
The aim of the present study was to investigate associations between hippocampal subfield volumes and plasma levels of brain-derived neurotrophic factor (BDNF) in patients experiencing a first episode of major depression (MD) (n = 30) as compared to healthy controls (HC) (n = 49). Covariate-adjusted linear regression was performed to compare the MD and healthy groups, adjusting for age, sex, and total estimated intracranial volume. We demonstrated that there were no differences in total hippocampal volume between the MD and HC groups. However, the volumes of the hippocampus-amygdala-transition-area (HATA) on the left side of the brain as well as the parasubiculum, presubiculum, and fimbria on the right side were statistically significantly smaller in the MD group than in the HC group. Furthermore, the volume of the hippocampal fissure on the right side was statistically significantly smaller in the HC group than in the MD group. In the MD group, we found a positive linear correlation between hippocampal volume and plasma BDNF concentrations in the CA4 area on the left side (p = 0.043). In contrast, in the HC group, we found a negative linear correlation between parasubiculum volume on the right side and plasma BDNF concentrations (p = 0.04). These results suggest that some hippocampal subfields may already be atrophic at the start of MD. In addition, our findings suggest that the sensitivity of the right parasubiculum region to BDNF may differ between MD and HC groups. These findings guide future research directions and, if confirmed, may ultimately inform medical guidelines.